2022
DOI: 10.3390/diagnostics12020335
|View full text |Cite
|
Sign up to set email alerts
|

OCT-Guided Surgery for Gliomas: Current Concept and Future Perspectives

Abstract: Optical coherence tomography (OCT) has been recently suggested as a promising method to obtain in vivo and real-time high-resolution images of tissue structure in brain tumor surgery. This review focuses on the basics of OCT imaging, types of OCT images and currently suggested OCT scanner devices and the results of their application in neurosurgery. OCT can assist in achieving intraoperative precision identification of tumor infiltration within surrounding brain parenchyma by using qualitative or quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 122 publications
(223 reference statements)
0
15
0
Order By: Relevance
“…OCT is a promising method of intraoperative navigation in brain glioma surgery ( 28 30 ). The OCT data can be analyzed qualitatively ( 62 64 ) and quantitatively ( 26 , 27 , 64 ), but preference is generally given to color-coding of the OCT signal using the attenuation coefficients ( 26 28 ). In this paper, we used OCT/CP OCT to visualize GBM7-Luc2-mKate2 PDXs in mouse brain and found that tumor can be differentiated from the normal white matter using optical coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…OCT is a promising method of intraoperative navigation in brain glioma surgery ( 28 30 ). The OCT data can be analyzed qualitatively ( 62 64 ) and quantitatively ( 26 , 27 , 64 ), but preference is generally given to color-coding of the OCT signal using the attenuation coefficients ( 26 28 ). In this paper, we used OCT/CP OCT to visualize GBM7-Luc2-mKate2 PDXs in mouse brain and found that tumor can be differentiated from the normal white matter using optical coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, surgeons may employ the adjuncts based on their own expertise with various technologies, tumor histology and location, and cost-effectiveness. Other intraoperative modalities include fluorescence using indocyanine green, which demonstrated an increased affinity to endothelial cells in the peritumoral tissue [ 97 ], theranostics using optical coherence tomography that improved resection at a cellular-level precision [ 98 ], and other imaging modalities such as stereotactic navigation [ 99 ], whole-brain tractography, and diffusion tensor imaging [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative approach is based on visual analysis of structural two-dimensional OCT images, which is considered subjective. However, this method is still the only one available for use in clinical practice in several countries (19). The quantitative approach to the analysis of OCT images is based on the calculation of optical coefficients, where the attenuation coefficient is frequently used for this purpose (14,16,20).…”
Section: Introductionmentioning
confidence: 99%